TATWIR WASIILATU TA’LIIMI ALMUFRODAAT ‘ALA DHOUI ANDROID BISTIKHDAAMI KODULAR LITALAAMIZI ALMADROSATI ALIBTIDAIYYATI ALMUHAMMADIYYATI JOPANG MANGANTI - Muhammad Rahmad; M. Yusuf Salam; Suharmon Suharmon; Partomuan Harahap (Universitas Islam Negeri Mataram, 2024)
The main problem in this research is the lack of use of learning media which results in students' lack of attention to Arabic language learning. This research aims to (1) find out what students' needs are for Android-based Arabic vocabulary learning media using codular (2) find out the validity of the learning media developed; and (3) knowing the practicality of the learning media being developed. This research is research and development by adapting the 4-D model, namely define, design, development, disseminate. The research instruments used were interview sheet instruments, validation sheets, and practicality sheets. The data analysis technique used is descriptive statistical analysis. The results of this research are android-based Arabic vocabulary learning media for Arabic language lessons at Muhammadiyah Fullday Jopang Manganti Elementary School, especially for class III. This learning media consists of five discussions, each discussion consisting of mufradat, images, sounds, and exercises to support student learning. The research results show that (1) the average results show that students need Android-based Arabic vocabulary learning media using Kodular to support Arabic language learning in class III with a percentage of 100%. (2) the results of research validation analysis by three validators obtained an average learning media validation of 3.92 with a very valid category. (3) the results of trials conducted on 17 students and 1 Arabic language teacher also obtained results with an average score of 3.92 in the very practical category